2015
DOI: 10.3390/nu7115440
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of in Vivo Colonic Short Chain Fatty Acid Production from Inulin

Abstract: Short chain fatty acids (SCFA), including acetate, propionate, and butyrate, are produced during bacterial fermentation of undigested carbohydrates in the human colon. In this study, we applied a stable-isotope dilution method to quantify the in vivo colonic production of SCFA in healthy humans after consumption of inulin. Twelve healthy subjects performed a test day during which a primed continuous intravenous infusion with [1-13C]acetate, [1-13C]propionate and [1-13C]butyrate (12, 1.2 and 0.6 μmol·kg−1·min−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(87 citation statements)
references
References 61 publications
5
81
0
1
Order By: Relevance
“…9 It could be suggested that the elevated ratio of colonic propionate : acetate promoted by IPE supplementation may have prevented the accumulation of liver fat observed in the inulin-control group by impairing hepatic acetate metabolism. This proposed mechanism is concordant with the results from Wolever and colleagues, who showed using stable isotope technology that propionate inhibits incorporation of colonic [1,[2][3][4][5][6][7][8][9][10][11][12][13] C] acetate into plasma lipids in humans. 7 Studies using rat hepatocytes have also highlighted that propionate inhibits lipid synthesis when acetate is a major source of acetyl-CoA.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…9 It could be suggested that the elevated ratio of colonic propionate : acetate promoted by IPE supplementation may have prevented the accumulation of liver fat observed in the inulin-control group by impairing hepatic acetate metabolism. This proposed mechanism is concordant with the results from Wolever and colleagues, who showed using stable isotope technology that propionate inhibits incorporation of colonic [1,[2][3][4][5][6][7][8][9][10][11][12][13] C] acetate into plasma lipids in humans. 7 Studies using rat hepatocytes have also highlighted that propionate inhibits lipid synthesis when acetate is a major source of acetyl-CoA.…”
Section: Resultssupporting
confidence: 90%
“…The blood samples were collected >12 hours after volunteers were requested to ingest their final supplement, which may explain why we were unable to detect large differences in circulating SCFAs postsupplementation. Nevertheless, previous research using stable isotope methodology has showed that inulin is predominantly fermented in the human colon into acetate (82%), with considerably less propionate and butyrate produced (6% and 12%, respectively) . Dietary supplementation with inulin‐type fructans (ITF) has generally been associated with positive effects on metabolic health.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the RA and location of BPB species likely has an important impact on the amount of butyrate produced in the colon, other factors such as diet can play a large role. For instance, soluble fibers with high degrees of polymerization, such as inulin, are fermented in the gut which results in SCFA production [71-73]. Using a limited dietary questionnaire, our study observations suggest that HIV-1 infection may disrupt the normal association between diet and RA of BPB species, thereby potentially contributing to the dysbiosis of the intestinal microbiome seen during HIV-1 infection.…”
Section: Discussionmentioning
confidence: 96%
“…First, undigested carbohydrates are broken down into smaller carbonhydrates by microbial hydrolysis, which is mainly done by Bifidobacterium in the large intestine. The monosaccharides are then fermented to phosphoenolpyruvate (PEP) by the Embden-Meyerhof-Parnas pathway (Boets, Deroover et al 2015). The Embden-Meyerhof-Parnas pathway is the major pathway of glycolysis, and this pathway will convert monosaccharides to PEP which are then converted into pyruvate by pyruvate kinase in glycolysis (White, Drummond et al).…”
Section: Inulin In Digestive Systemmentioning
confidence: 99%